Synthesis of (R)-{eta(6)-[O-methyl-N-(alpha-methylbenzyl)hydroxyamino]-benzene} chromium tricarbonyl via nucleophilic aromatic substitution of (eta(6)-fluorobenzene) chromium tricarbonyl - da Costa, M; Curto, M; Davies, S; Sanders, J; Teixeira, F (2001)
Chiral hydroxylamine chromium tricarbonyl complexes may be prepared in satisfactory to reasonable yieldvia nucleophilic aromatic substitution of the anion derived from N,O-substituted hydroxylamines and (η6-fluorobenzene) chromium tricarbonyl. The enantiomerically pure complex (R)-{η6-[O-methyl-N-(α-methylbenzyl)hydroxyamino]- benzene} chromium tricarbonyl 6a was characterised by X-ray crystallography.